Analisis Model-Model Pembelajaran Informatika di SMP: Kajian Kepustakaan - Jelvi Rozi; Jufri Jufri (Departement of Mathematics Education, 2024)
Abstract This research aims to analyze various informatics learning models applied in Junior High School (SMP) based on literature review. The research method used is literature method by collecting and analyzing various relevant sources from journals, books, and research reports. The results show that project-based learning, flipped classroom, and blended learning models are the most effective models in improving students' understanding and skills in informatics subjects. However, each model has advantages and disadvantages that need to be considered in its implementation.